Association of IFNG gene methylation in peripheral blood cells with the development and prognosis of autoimmune thyroid diseases. (November 2019) - Hashimoto, Hidemi; Watanabe, Mikio; Inoue, Naoya; Hirai, Nachi; Haga, Emi; Kinoshita, Riku; Hidaka, Yoh; Iwatani, Yoshinori
Highlights: Interferon gamma ( IFNG ) methylation and the circadian and daily variations. Methylation levels of IFNG −54 CpG were higher in intractable Graves' disease. The methylation levels were not different between severe and mild Hashimoto's disease. IFNG −54 methylation levels in IFNG −2019 T carriers were higher in intractable GD. Negative correlation between IFNG −54 CpG methylation and ages in HD. Abstract: The intractability of Graves' disease (GD) and the severity of Hashimoto's disease (HD) vary among patients. Both genetic and environmental factors may be associated with their prognoses. To clarify the role of methylation of the IFNG gene in the pathogenesis and prognosis of (AITDs), we examined interferon gamma (IFNG) methylation levels at various CpG sites and genotyped IFNG +874 A/T and +2109 C/T polymorphisms. We analyzed methylation 59 patients with HD, 57 patients with GD and 26 healthy volunteers by pyrosequencing. We genotyped IFNG gene polymorphisms from 207 patients with GD, 208 patients with HD, and 102 healthy controls. The methylation levels of IFNG −54 CpG were higher in patients with intractable GD than in those with GD in remission, but there was no difference between patients with severe and mild HD. In carriers of IFNG +2109 T (CT + TT) (85.5% in controls), the −54 CpG methylation levels were significantly higher in patients with intractable GD than in those with GD in remission. On the other hand, in carriers of IFNG +2109 CC, the −4293 CpG methylation levels were higher in intractable GD patients. The methylation levels of IFNG −54 CpG and −4293 CpG were negatively correlated with the age in HD, especially severe HD, patients and GD patients, respectively. There was no circadian variation but considerable daily variation in the methylation levels of IFNG −54 CpG. In conclusion, both the methylation levels of CpG sites and the functional polymorphisms in the IFNG gene were associated with the pathogenesis and prognosis of AITD, especially with GD intractability.